Erdheim-Chester disease: A case report - Petrović Stanko; Doder Radoje; Perišić Nenad; Petrović Marijana; Brčerević Irina; Roganović Branka (Vojnosanitetski Pregled)
Introduction. Erdheim-Chester disease (ECD) is a rare non-Langerhans-cell histiocytosis. About 500 cases are published so far. It is multisystemic disease characterised by bilateral symmetric long bones sclerosis. Main histopathological finding is accumulation of big foamy histiocytes, immunohistochemically positive to CD68, and negative to S-100 and CD1a. There are no guidelines that reliably identify population that requires therapy, but symptomatic ECD, organ failure and central nervous system involvement re-quire treatment. Case report. We described a patient with a multisystemic form of ECD affecting long bones, the hypophysis, abdomen, and the peripheral nerves. Five years after initial symptoms ECD was suspected. Prednison was initiated, 60 mg once a day. After obtaining the diagnosis of ECD, interferon alpha 2A was introduced, but soon after stopped due to severe side effects. Considering that histiocytes were positive to platelet derived growth factor receptor alpha (PDGFR alpha) imatinib mesylate was started, but after two months stopped due to no clinical and radiological improvement. The disease was worsening and the patient died. Conclusion. We described the patient with intraperitoneal form of ECD, without cardiac and pulmonary involvement. There are several important issues: the diagnosis of ECD could be difficult to make, three treatment regimens were included and the patient died nine years after the initial symptoms due to indolent course of the disease and unsuccessful treatment.